Religious Disagreement, Religious Experience, and the Evil God Hypothesis - Lougheed, Kirk (European journal for philosophy of religion, 2020)
Conciliationism is the view that says when an agent who believes P becomes aware of an epistemic peer who believes not-P, that she encounters a (partial) defeater for her belief that P. Strong versions of conciliationism pose a sceptical threat to many, if not most, religious beliefs since religion is rife with peer disagreement. Elsewhere (Removed) I argue that one way for a religious believer to avoid sceptical challenges posed by strong conciliationism is by appealing to the evidential import of religious experience. Not only can religious experience be used to establish a relevant evidential asymmetry between disagreeing parties, but reliable reports of such experiences also start to put pressure on the religious sceptic to conciliate toward her religious opponent. Recently, however, Asha Lancaster-Thomas poses a highly innovative challenge to the evidential import of religious experience. Namely, she argues that an evil God is just as likely to explain negative religious experiences as a good God is able to explain positive religious experiences. In light of this, religious believers need to explain why a good God exists instead of an evil God. I respond to Lancaster-Thomas by suggesting that, at least within the context of religious experience, (i) that the evil God hypothesis is only a challenge to certain versions of theism; and (ii) that the existence of an evil God and good God are compossible.